2015
DOI: 10.3382/ps/pev271
|View full text |Cite
|
Sign up to set email alerts
|

Genetically modified crops in a 10-generation feeding trial on Japanese quails — Evaluation of its influence on birds’ performance and body composition

Abstract: The effect of genetically modified (GM) feed components comprising soya bean meal and maize on the performance indices (reproduction, survival rate, growth, egg production, relative weight of chosen internal organs, and basic chemical composition of breast muscle and egg yolk) of Japanese quails was investigated during a 10-generation trial. A total number of 8,438 healthy quail chicks were used in the course of the trial. In each generation, birds were maintained in 3 experimental groups differing in the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Since the chickens of both groups received the same feed rate, respectively, its costs per 1 kg of growth in the first 4 and 8 weeks were lower in the experimental group by 3.2-3.7%, and for the entire period of the experiment (0-17 weeks) -by 2.9%. The following results on the feeding of chickens with GM feed were confirmed in studies on the feeding of quails for 10 generations of feed containing GM maize (Sartowska et al, 2015).…”
Section: Resultsmentioning
confidence: 54%
“…Since the chickens of both groups received the same feed rate, respectively, its costs per 1 kg of growth in the first 4 and 8 weeks were lower in the experimental group by 3.2-3.7%, and for the entire period of the experiment (0-17 weeks) -by 2.9%. The following results on the feeding of chickens with GM feed were confirmed in studies on the feeding of quails for 10 generations of feed containing GM maize (Sartowska et al, 2015).…”
Section: Resultsmentioning
confidence: 54%
“…In an earlier 90-day safety assurance study with rats fed borer-protected maize, there were also no test article related changes in haematology parameters for the MON 810 maize fed animals (10). A series of Polish studies led the author to conclude that dietary GM maize did not affect the haematological parameters of pigs (23), Japanese quails (21), broiler chickens, or laying hens (25, 26). In the present investigation, blood creatinine concentration increased significantly in rats fed the GM diets.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found no difference in the productive performance or health of any beef cattle ( Erickson et al., 2003 ), dairy cattle ( Grant et al., 2003 ; Ipharraguerre et al., 2003 ; Combs and Hartnell, 2008 ), broiler ( Kan and Hartnell, 2004 ; Taylor et al., 2007a , 2007b , 2007c ); McNaughton et al. 2011 ), sheep ( Hartnell et al., 2005 ) or quail ( Sartowska et al., 2015 ) fed on GT-based feedstuffs. These analyses concerning livestock, however, do not address potential reproductive issues related to glyphosate or GBHs.…”
Section: Productive Performances Of Animals Fed On Gt Cropsmentioning
confidence: 99%
“…Unfortunately, very few studies have investigated the effects of these exposures on agriculturally important animals, and the majority of those that have, have given no concern to reproductive health and performance ( Erickson et al., 2003 ; Grant et al., 2003 ; Ipharraguerre et al., 2003 ; Taylor et al., 2007a , 2007b ; Kan and Hartnell, 2004 ; Hartnell et al., 2005 ; Combs and Hartnell, 2008 ; McNaughton et al. 2011 ; Sartowska et al., 2015 ). This is due, in part, to the fact that for an overwhelming majority of any livestock population, the reproductive health and performance is of no concern for a producer.…”
Section: Gbh As Potential Threat To Reproductive Health Of Livestockmentioning
confidence: 99%